1972
DOI: 10.1172/jci107042
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation with end-expiratory pressure in acute lung disease

Abstract: Pao, and compliance is recruitment of gas exchange airspaces and prevention of terminal airway closure.Address reprint requests to Dr. Pontoppidan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
2
15

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(125 citation statements)
references
References 20 publications
3
105
2
15
Order By: Relevance
“…This is consistent with the findings in normal subjects [32] and in ARDS patients [22,23,28,29] obtained over a larger PEEP range, but contrasts with the results of FALKE et al [25], who found a decrease in static elastance (Est) with PEEP of 5 cmH 2 O. The lack of Ers,st changes with PEEP in the present patients is not surprising because, like normal subjects, they did not exhibit an inflection point on the static inflation V-P curve (figs.…”
Section: Elastance and Resistancesupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with the findings in normal subjects [32] and in ARDS patients [22,23,28,29] obtained over a larger PEEP range, but contrasts with the results of FALKE et al [25], who found a decrease in static elastance (Est) with PEEP of 5 cmH 2 O. The lack of Ers,st changes with PEEP in the present patients is not surprising because, like normal subjects, they did not exhibit an inflection point on the static inflation V-P curve (figs.…”
Section: Elastance and Resistancesupporting
confidence: 90%
“…1 and 2). According to some authors [25][26][27], in ARDS patients without AIDS and PCP the inflection point is a common occurrence, though this might not be particularly frequent according to other studies [22,[28][29][30]. It has been suggested that the inflection is present in the earliest stage of ARDS, whereas later on, probably as a result of oedema resolution, the inflection disappears with or without increases or decreases in elastance, probably depending on the pattern of fibrosis development [26].…”
Section: Static Inflation V-p Curvementioning
confidence: 99%
“…However, life-threatening complications such as pneumothorax occurred and mortality was high [65]. With the introduction of positive end-expiratory pressure (PEEP), oxygen uptake improved and the incidence of pneumothoraces in ARDS patients was reduced dramatically [66][67][68]. In addition, Hickling et al observed that ventilation with a lower Vt (i.e.…”
Section: Mechanical Ventilationmentioning
confidence: 99%
“…The adult respiratory distress syndrome, later called acute respiratory distress syndrome (ARDS), became the prototype pathology accompanying the development of intensive care medicine (5) and PEEP was one of the most widely used therapeutic approaches. The first studies on mechanisms of PEEP during ARDS were performed by Falke and colleagues at the Massachusetts General Hospital (6), while the most popular clinical approach for PEEP setting was proposed by Suter as a function of oxygen transport and respiratory mechanics (7). In the meantime, Kirby and colleagues, from Miami, proposed the use of a "super PEEP" , that is PEEP up to 25 cmH 2 O, somehow forerunner of the "open lung approach" (8).…”
Section: Introductionmentioning
confidence: 99%